Сorrelation of National State Infl uence and Power of the Market in the Mission Formation of the Modern University - Kolotylo, Mariana (Filosofiya osvity. Philosophy of Education, 2011)
The article deals with the problem of mission transformation in the light of contemporary globalization processes. In particular, the matter is that universities are in crisis of their identity in the connection with changes of modern economic and socio-cultural area. The main focus is concentrated on the trend to reduction of the role and importance of the national state in University mission formation and the increase of market power infl uence on it. The author identifi es the ways of overcoming the crisis for Universities, appealing to the need for active participation of the nation-state in the fate of the Universities.